2000
DOI: 10.1108/10610420010316339
|View full text |Cite
|
Sign up to set email alerts
|

The verbal and visual components of package design

Abstract: It is estimated that 73% of purchase decisions are made at point of sale ('Frontiers; planning for consumer change in Europe 1996/1997', Henley Centre, 1996

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
209
1
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(227 citation statements)
references
References 25 publications
6
209
1
11
Order By: Relevance
“…They investigated several unanswered questions in recent studies of consumer behavior in the context of internet-based marketing. The results of an empirical study of econsumer behavior demonstrated that brand trust was achieved through the following dimensions such as various brand experiences and the search for information, a high level of brand familiarity, and customer satisfaction based on cognitive and emotional factors (Rettie & Brewer, 2000;Chattopadhyay & Laborie, 2005). Dickson and Urbany (1994) investigated retailer reactions to competitive price changes.…”
Section: Introductionmentioning
confidence: 99%
“…They investigated several unanswered questions in recent studies of consumer behavior in the context of internet-based marketing. The results of an empirical study of econsumer behavior demonstrated that brand trust was achieved through the following dimensions such as various brand experiences and the search for information, a high level of brand familiarity, and customer satisfaction based on cognitive and emotional factors (Rettie & Brewer, 2000;Chattopadhyay & Laborie, 2005). Dickson and Urbany (1994) investigated retailer reactions to competitive price changes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefor, illustration is a critical complement to the headline and body copy of an advertisement, and assists the consumers' information processing and decision making [15]. Though researchers advocated the positive influence of illustration and using pictorial materials in an advertisement, the most studies of illustrations of advertisements concentrate on the visual component such as size, color, and format of the ads [27]- [30]. Regarding the study of hotel advertisements, Siu and Fung (1998) classified seven common used illustrations, namely the staff of the hotel, the general manager or top management of the hotel, customers of the hotel, exteriors of the hotel, interior of the hotel without people, interiors of the hotel with people, and others [15].…”
Section: Illustrations Of Advertisementsmentioning
confidence: 99%
“…Packaging is the opening bridge way between a brand and its communication with customers, and under the rising competitive market, the status of product design has now risen to a major role in marketing (Rettie and Brewer, 2000). The main function for packaging has been to safely protect the product and ensure it can be conveniently maneuvered during transport, storage, sales, and usage(Gonzalez, Thorhsbury & Twede, 2007;Wells et al, 2007;Kuvykaite, 2001 ) .…”
Section: Figure1mentioning
confidence: 99%